Species distribution and antifungal susceptibility patterns of Candida spp. bloodstream isolates from a Brazilian tertiary care hospital - Passos, Xisto Sena; Costa, Carolina Rodrigues; Araujo, Crystiane Rodrigues; Nascimento, Elisa Sales; Hasimoto e Souza, Lucia Kioko; Lisboa Fernandes, Orionalda de Fatima; Sales, Werther Souza; Rodrigues Silva, Maria do Rosario (Springer, 2007)
In this work, we collect data from surveys of bloodstream Candida isolates performed in Brazil from 1996 to 2004. Besides, we analyzed the species distribution of bloodstream Candida isolates together with potential risk factors for candidemia and the susceptibility profile of these isolates in patients from Hospital das Clinicas in Goiaonia city, Brazil. Blood samples were collected in the admission day and on every 7 days, in the intensive care unit (ICU) of a tertiary hospital. Candida isolates were identified by standard protocols that included germ tube formation, chlamydoconidia production on cornmeal agar and sugar fermentation and assimilation tests. Data of patients were recorded and analyzed according to age at the time of diagnosis, gender and presence of potential risk factors. Statistical analysis was used to determine if the time of hospital permanence increased Candida colonization in ICU patients' blood. The antifungal susceptibility testing was performed by broth microdilution method according to document NCCLS/CLSI M27-A2. Among the 345 blood samples cultured, candidemia was recovered in 33 patients, which were isolated 51.5% of Candida non-albicans. Fungemia was associated with long-term hospitalization. Fluconazole, itraconzole, voriconazole and amphotericin B exhibited a potent activity against all isolates of Candida. Voriconazole MICs were much low for all isolates tested. This work confirms data of increase of Candida non-albicans species in bloodstream in ICU and shows that voriconazole in vitro activity was higher than those of itraconazole, fluconazole and amphotericin B.
Keywords: antifungal; candidemia; intensive care unit; risk factors; susceptibility testing